Using DNA Barcode matK and ITS in Molecular Identification of the Anoectochilus roxburghii (Wall.) Wall. ex Lindl. 1840 Plant Collected in Luang Namtha, Laos - Nhan, Pham Thi Thanh (VNU Journal of Science: Natural Sciences and Technology; Vol 42 No 2, 2025)
The Anoectochilus roxburghii (Wall.) Wall. ex Lindl. 1840 species has been over-exploited and is listed in the Red Data Book of Vietnam. In this article, we present the identification results of the species collected from Luang Namtha province, Laos, using DNA barcodes ( matK and ITS ). The matK gene fragment and the ITS region isolated on the agarose gel had lengths consistent with theoretical calculations, approximately 900 bp and 500 bp, respectively. The BLAST analysis of the matK gene and ITS region obtained in this study has the highest similarity - 100% and 98.39%, respectively - to Anoectochilus roxburghii and Anoectochilus burmannicus species in the GenBank. Each sequence exhibits 15 nucleotide position variations compared to the reference sequences. The results of molecular phylogenetic analysis demonstrated that the matK and ITS barcodes identified the geneus Anoectochilus , in which, ITS region can be used for differentiation of the Anoectochilus roxburghii species.